2017
DOI: 10.18632/oncotarget.22083
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of CAPN2 promotes cell metastasis and proliferation via AKT/mTOR signaling in renal cell carcinoma

Abstract: The calpain 2 (CAPN2) is upregulated in various malignant carcinomas. Previous studies have reported that CAPN2 functioned as an oncogenic factor in human cancers. However, its clinical role and potential effects on cell metastasis and proliferation in renal cell carcinoma (RCC) remain unknown. In this study, we evaluated the mRNA and protein levels of CAPN2 in human RCC specimens, matched normal specimens, and RCC cell lines using quantitative Real-time PCR (RT-PCR) and western blot. Immunohistochemistry of 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…In MeCP2 ChIP-Seq in MDA-MB-468 cells, we found that MeCP2 binds to multiple novel targets not previously associated with MeCP2 function in the context of breast cancer. Some of these included the following genes: a) SSU72 Homolog, RNA Polymerase II CTD Phosphatase (SSU72), a protein phosphatase that catalyzes the dephosphorylation of the C-terminal domain of RNA polymerase II ( 66 ); b) CAPN2 (Calpain 2), a calcium-sensitive cysteine protease ( 67 ); c) Plexin B2 (PLXNB2), a class B transmembrane receptor that participates in axon guidance and cell migration in response to semaphorins ( 68 ); d) Zinc Finger SWIM-Type Containing 4 (ZSWIM4); e) RUNX Family Transcription Factor 3 (RUNX3) a transcription factor that functions as a tumor suppressor and is frequently deleted or transcriptionally silenced in cancer ( 69 , 70 ), and f) Solute Carrier Family 45 Member 4 (SLC45A4) ( Figure 1B ). Additionally, in MCF7 some of the notable genes included a) Ubiquitin Specific Peptidase 34 (USP34), a ubiquitin hydrolase that removes conjugated ubiquitin from AXIN1 and AXIN2, acting as a regulator of Wnt signaling pathway ( 71 ); b) Maltase–Glucoamylase (MGAM), an enzyme that plays a role in the digestion of starch ( 72 ); c) GDP-Mannose 4,6-Dehydratase (GMDS), an enzyme that participates in the synthesis of GDP-fucose from GDP-mannose ( 73 ); d) Solute Carrier Family 45 Member 4 (SLC45A4); e) CCDC26 Long Non-Coding RNA (CCDC26), a lncRNA class associated with Malignant Glioma and Astrocytoma ( 74 , 75 ); and f) Sidekick Cell Adhesion Molecule 1 (SDK1) ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In MeCP2 ChIP-Seq in MDA-MB-468 cells, we found that MeCP2 binds to multiple novel targets not previously associated with MeCP2 function in the context of breast cancer. Some of these included the following genes: a) SSU72 Homolog, RNA Polymerase II CTD Phosphatase (SSU72), a protein phosphatase that catalyzes the dephosphorylation of the C-terminal domain of RNA polymerase II ( 66 ); b) CAPN2 (Calpain 2), a calcium-sensitive cysteine protease ( 67 ); c) Plexin B2 (PLXNB2), a class B transmembrane receptor that participates in axon guidance and cell migration in response to semaphorins ( 68 ); d) Zinc Finger SWIM-Type Containing 4 (ZSWIM4); e) RUNX Family Transcription Factor 3 (RUNX3) a transcription factor that functions as a tumor suppressor and is frequently deleted or transcriptionally silenced in cancer ( 69 , 70 ), and f) Solute Carrier Family 45 Member 4 (SLC45A4) ( Figure 1B ). Additionally, in MCF7 some of the notable genes included a) Ubiquitin Specific Peptidase 34 (USP34), a ubiquitin hydrolase that removes conjugated ubiquitin from AXIN1 and AXIN2, acting as a regulator of Wnt signaling pathway ( 71 ); b) Maltase–Glucoamylase (MGAM), an enzyme that plays a role in the digestion of starch ( 72 ); c) GDP-Mannose 4,6-Dehydratase (GMDS), an enzyme that participates in the synthesis of GDP-fucose from GDP-mannose ( 73 ); d) Solute Carrier Family 45 Member 4 (SLC45A4); e) CCDC26 Long Non-Coding RNA (CCDC26), a lncRNA class associated with Malignant Glioma and Astrocytoma ( 74 , 75 ); and f) Sidekick Cell Adhesion Molecule 1 (SDK1) ( Figure 1C ).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that MeCP2 binds to genomic regions devoid of CpG methylation such as for USP34, MGAM, GMDS, SLC45A4, SSU72, CAPN2 and PLXN2 ( Figures S1B–C ). Similarly, while these are novel targets of MeCP2, many have been implicated in diverse cancers ( 67 , 71 , 88 92 ). This further shows the complexity of MeCP2 binding across the genome.…”
Section: Resultsmentioning
confidence: 99%
“…Mechanistically, LINC00263 increases CAPN2 expression by functioning as a ceRNA of miR-147a, and thus potentiates malignant capabilities. CAPN2 is a calcium-dependent protease that is highly upregulated in various cancers (32). CAPN2 is known to play an important role in proliferation and metastasis of cancer cells (33), and it was also reported to function as an oncogene by inducing EMT and increasing expression of matrix metalloproteinase 9 (MMP9) (32, 34).…”
Section: Discussionmentioning
confidence: 99%
“…Targeted EGFR drugs, such as gefitinib, appear to be effective for approximately 1 year, but resistance is inevitably developed shortly after this period. CAPN2 has been demonstrated to serve a role in altering the cellular response to certain cancer therapies ( 9 , 10 , 19 ). However, the events and mechanisms involved in these processes remain incompletely understood.…”
Section: Discussionmentioning
confidence: 99%